Nilai-Nilai Tasawuf dalam Konsep Pendidikan Islam Menurut Hamka Roza Susanti - Susanti, Roza (JOEAI (Journal of Education and Instruction), 2021)
The purpose of this study is to understand the values ​​of Sufism in Islamic education according to Hamka. This research is a qualitative research using a library research approach using books and other literatures as the main object of research, for further content analysis that will be used in drawing conclusions. The results of the research, Hamka is an Islamic thinker who is famous for his concept of "Modern Sufism". Hamka did not create a new concept in Sufism, he only wanted to restore the meaning of Sufism as it was at the beginning of Sufism, namely cleansing the soul from all heart diseases, educating, increasing the degree of mind, suppressing all greed and fighting excessive lust from the need for true happiness. In conclusion, Hamka's thoughts on Islamic education are in line with the concept of modern Sufism that he put forward. This is clearly seen in his opinion on the objectives and materials of Islamic education. According to Hamka, the goal of Islamic education is to create a complete human being (insan kamil). While the Islamic education materials recommended by Hamka are qana'ah, syaja'ah, iffah and tawakkal. Keywords: Sufism values, Islamic Education Concept, Hamka